Education for Sentenced Minors and Young Adults — Introduction to an Ongoing European Project and Results of a Questionnaire - Fekete, Márta; Hegedűs, Judit (Magyar Rendészet, 2016)
The article is an introduction to an ongoing European project in which representatives of Hungary took part for a year in 2015. The project focuses on in-prison education of sentenced minors and young adults in order to them being more employable and motivated in their lives and work. The Hungarian team (researchers and academics of the National University of Public Service, Eötvös Loránd University and FORESEE Research Group) is responsible for providing the scientific background of the project, which is now in the phase of implementation of a chosen educational methodology. The authors in this article would like to provide an hors d’oeuvre to the reader with presenting the results of a questionnaire distributed among minors during the summer of 2015, based on which the methodology has been chosen.